Chromatin loops are an ancestral hallmark of the animal regulatory genome - Iana V. Kim; Cristina Navarrete; Xavier Grau-Bové; Marta Iglesias; Anamaria Elek; Grygoriy Zolotarov; Nikolai S. Bykov; Sean A. Montgomery; Ewa Księżopolska; Didac Cañas-Armenteros; Joan J. Soto-Angel; Sally P. Leys; et al. (Nature, 2025)
Abstract In bilaterian animals, gene regulation is shaped by a combination of linear and spatial regulatory information. Regulatory elements along the genome are integrated into gene regulatory landscapes through chromatin compartmentalization1,2, insulation of neighbouring genomic regions3,4 and chromatin looping that brings together distal cis-regulatory sequences5. However, the evolution of these regulatory features is unknown because the three-dimensional genome architecture of most animal lineages remains unexplored6,7. To trace the evolutionary origins of animal genome regulation, here we characterized the physical organization of the genome in non-bilaterian animals (sponges, ctenophores, placozoans and cnidarians)8,9 and their closest unicellular relatives (ichthyosporeans, filastereans and choanoflagellates)10 by combining high-resolution chromosome conformation capture11,12 with epigenomic marks and gene expression data. Our comparative analysis showed that chromatin looping is a conserved feature of genome architecture in ctenophores, placozoans and cnidarians. These sequence-determined distal contacts involve both promoter–enhancer and promoter–promoter interactions. By contrast, chromatin loops are absent in the unicellular relatives of animals. Our findings indicate that spatial genome regulation emerged early in animal evolution. This evolutionary innovation introduced regulatory complexity, ultimately facilitating the diversification of animal developmental programmes and cell type repertoires.